Prognostic criteria for assessing complicated course of COVID-19 coronavirus infection - Shpadaruk, Katsiaryna; Smolyakova, Raisa; Molchan, Alla; Lozinskaya, Olga; Gapeenko, Elena (Journal of the Belarusian State University. Ecology, 2024)
The article analyzes in the dynamics of complex treatment disturbances in homeostasis diagnosed in patients with a favorable prognosis and with a complicated course of coronavirus infection SARS-CoV-2, who received treatment at the Republican Clinical Hospital for Disabled Persons of the Great Patriotic War named after P.M. Masherov" in 2020-2021. The first group (n = 100) included patients with a complicated course of coronavirus infection and a favorable prognosis; the second group (n = 100) included patients with a complicated course of COVID-19 and a poor prognosis. The control group (n = 70) consisted of persons who had no pathology according to clinical and anamnestic data during the examination period. In all groups, the subjects were comparable in age and gender. Hematological studies were performed in patients with coronavirus infection in the dynamics of complex treatment on the 1st, 5th and 10th day. Analysis of the data obtained showed statistically significant differences (p < 0.05) in the studied cellular indicators of peripheral blood (ESR level, total leukocyte content, relative content of band neutrophils, segmented neutrophils, lymphocytes) and integral hematological indicators of the body’s cellular reactivity (leukocyte ratio and rate index erythrocyte sedimentation rate (ILSE), Kalf-Kalif leukocyte intoxication index (LII), neutrophil-monocyte ratio index (MNRI), neutrophil-lymphocyte ratio index (NLRI) in relation to the control on the 10th day of observation. Based on the study of the dynamics of integral indicators of homeostasis, a new clinical and laboratory system has been developed for assessing the severity of the general functional state of the body, which makes it possible to predict the development of a systemic inflammatory response, a “neutrophil explosion” and increase the effectiveness of complex therapy in patients with coronavirus infection COVID-19.